Weight and configuration optimization of the launcher pod using finite element analysis. (July 2023) - Dewangan, Mithilesh Kumar; Panigrahi, S K
This paper deals with the stress analysis of the launcher pod based on optimization of its configuration and weight without compromising its strength and stiffness. The launcher pod assembly is a complex fabricated structure, which is subjected to a variety of dynamic loads during firing of rockets. A series of finite element simulations reveal the critical location of the pod for different loading conditions based on the stress magnitude, which helps to optimize its weight and configuration of the launcher pod. It has been observed that the optimized weight of the given launcher pod after modification of materials and configuration, with the provided materials, loading, and boundary conditions, is reduced by 36.27% (without launcher tubes and rockets) against the initial weight of the launcher pod.